2002
DOI: 10.1046/j.1320-5463.2002.01390.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of imidazolone, pentosidine and Nɛ‐(carboxymethyl)lysine in hippocampal CA4 pyramidal neurons of aged human brain

Abstract: Previous studies from our laboratory demonstrated that N(epsilon)-(carboxymethyl)lysine (CML), one of the major advanced glycation end products (AGE), was accumulated in human pyramidal neurons in the hippocampus in an age-dependent manner. This suggests a potential link between AGE-accumulation and the aging process in neurons. The purpose of the present study was to examine whether this notion could be extended to other AGE structures, such as imidazolone and pentosidine. This was done using 19 human brains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 50 publications
0
21
0
2
Order By: Relevance
“…AGEs is a generic name for the final reaction products of proteins and sugars [18]. Molecular analysis has revealed that AGEs-modified proteins have several specific molecular motifs, such asN " -(carboxymethyl)lysine (CML), pentosidine, imidazoline, and pyrraline [4,5,7]. These AGEsspecific motifs are speculated to have different roles in the ageing process and diabetic complications [18].…”
Section: Introductionmentioning
confidence: 99%
“…AGEs is a generic name for the final reaction products of proteins and sugars [18]. Molecular analysis has revealed that AGEs-modified proteins have several specific molecular motifs, such asN " -(carboxymethyl)lysine (CML), pentosidine, imidazoline, and pyrraline [4,5,7]. These AGEsspecific motifs are speculated to have different roles in the ageing process and diabetic complications [18].…”
Section: Introductionmentioning
confidence: 99%
“…6) Thus, the design and discovery of inhibitors of AGEs formation can offer a promising therapeutic approach for the prevention of diabetic or other pathogenic complications. Aminoguanidine, a hydrazine-like small molecule, is the first AGEs inhibitor explored in clinical trials.…”
Section: Notesmentioning
confidence: 99%
“…It states that the AGEs induced cross-linking of proteins which leads to age-associated decline in the cellular functions (Monnier 1988;Brownlee 1995). It has also been found that the level of AGEs increases with age, which co-relates with the development of various age-related pathologies like Alzheimer's disease (Jono et al 2002) and dementia (Yaffe et al 2011). Hence, the process of glycation provides therapeutic target to alleviate AGE-mediated harmful effects observed in senescence.…”
Section: Discussionmentioning
confidence: 99%
“…The non-enzymatic glycation theory states that the levels of advanced glycation end products (AGEs) increase with age, which leads to decline in cellular functions (Monnier 1988;Brownlee 1995;Jono et al 2002;Yaffe et al 2011). AGEs are the structurally modified proteins or lipids produced by non-enzymatic process termed as glycation.…”
Section: Introductionmentioning
confidence: 99%